Macromycetes of the northern slope of mount El Cípil, on the south coast of Jalisco - Padilla-Velarde, Edgar Everardo; Zarco-Velazco, Georgina; Guzmán-Dávalos, Laura; Cuevas-Guzmán, Ramón (Instituto de Ecología, A.C., 2016)
Eighteen explorations were conducted from June to October of 2006 and 2007 to the northern slopes of mount El Cípil, located to the west of the municipality of Casimiro Castillo, on the south coast of the state of Jalisco, Mexico. In total, 441 fungal specimens were collected, of which 151 were identified, corresponding to 101 species, which belong to Ascomycota (12) and Basidiomycota (87) of the Fungi kingdom and to Myxogastrea (2) of the Protozoa kingdom. Although the results are preliminary, fifteen species are reported for the first time for the state of Jalisco, for which a brief description and illustrations of their main microscopic characters are provided. Furthermore, an analysis of the distribution of the species by plant communities and substrate, as well as information about their usefulness for man, is presented.